2017
DOI: 10.1038/eye.2016.304
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative clinical features of reactivated of Graves’ orbitopathy after orbital decompression

Abstract: PurposeTo investigate the incidence and preoperative clinical features of reactivated Graves' orbitopathy (GO) after orbital decompression.MethodsThis study included patients with GO who underwent orbital decompression for disfiguring proptosis and not compressive optic neuropathy and received postoperative follow-up care for more than 12 months. Patients who experienced active inflammatory signs within 6 months of decompression were excluded from analysis. The demographic characteristics, ophthalmic manifesta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
0
6
1
Order By: Relevance
“…Passive smoking has also been implicated in severe TED. [ 24 ] However, our case series did not show a correlation between smoking and worsening of eye disease. It is our practice to enquire about tobacco usage habits at the initial visit, and very firmly insist on the patient stopping use of tobacco.…”
Section: Discussioncontrasting
confidence: 62%
“…Passive smoking has also been implicated in severe TED. [ 24 ] However, our case series did not show a correlation between smoking and worsening of eye disease. It is our practice to enquire about tobacco usage habits at the initial visit, and very firmly insist on the patient stopping use of tobacco.…”
Section: Discussioncontrasting
confidence: 62%
“…There are a few modifications in the NOSPECS classification, in which the ophthalmic parameters used for its assessment are altered, the number of assessed parameters is reduced, or the scoring method is different [22][23][24][25] Jefferis et al discussed the results of the treatment of 55 patients (93 orbits) who underwent orbital decompression. In their studies, they presented data on the mean preoperative CAS, which was 1.4 ± 2.0 points before surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The greater the number of points in the NOSPECS classification, the more advanced the disease stage. There are a few modifications in the NOSPECS classification, in which the ophthalmic parameters used for its assessment are changed, the number of assessed parameters is reduced, or the scoring method is different [22][23][24][25].…”
Section: Methodsmentioning
confidence: 99%
“…The level of TSHR-Ab in serum which is related to the progression and severity of GO is different between smokers and nonsmokers after 2 and 6 months of radioiodine therapy [16]. Smoking affects the prognosis of GO and shortens the interval between orbital decompression and reactivation [17]. According to clinical practice guidelines, smoking cessation is highly recommended for GO patients [3] (Fig.…”
Section: Smokingmentioning
confidence: 99%
“…As a critical gene in T cell activation, cytotoxic T-lymphocyte-associated protein 4 (CTLA4) polymorphism plays a role in the pathogenesis of GO. One study detected CTLA-4 g.*642AT (8_33) polymorphism and found that [AT [16][17][18][19][20][21] ] homozygosity increases the risk and the severity of GO, but the [AA] genotype of CTLA-4 g.*6230G > A (rs3087243) has the opposite effect [79]. The frequency of genotype TT in rs733618 of CTLA4 is more common in a control group (OR = 0.421, p = 0.043) and the frequency of genotype CC and CT in rs16840252 of CTLA4 is also different between GO and control groups [80].…”
Section: Genetic Codesmentioning
confidence: 99%